Application of Thyroid Peroxidase (TPO) and Hector Battifora Mesothelial-1 (HBME-1) immunohistochemical markers in the diagnosis of papillary thyroid carcinoma of the thyroid - Singh, Vasundhara; Kaur Bagga, Permeet; Singh, Bikramjeet; Jaideep (International Journal of Medical Research and Review, 2020)
Background: Thyroid cancer is the most common endocrine malignancy accounting for >90% of malignancies of endocrine glands. The inter and intraobserver variation in the histomorphological diagnosis of Papillary Thyroid Carcinomas may sometimes pose a diagnostic difficulty. Application of IHC biomarkers may play an active or complementary role in their accurate classification. Aim: The present study was conducted to evaluate if HBME-1 and TPO immunohistochemical analysis can reliably differentiate papillary carcinomas from other thyroid lesions. Material and Methods: 50 cases of benign and malignant thyroid lesions were taken. Immunohistochemical staining for HBME-1 and TPO was performed. HBME-1 and TPO score was interpreted as absent and positive. Medical records were retrieved and their clinical data, surgical treatment, and pathological findings were noted. Results: Out of 50 cases, 19 (73.1%) cases were diagnosed PTC, 4 (15.4%) cases were FTC, 3(11.5%) cases were of MTC and 24 cases of benign thyroid lesions. TPO expression was found positive in 91.7% of cases of Benign thyroid lesions. In malignant thyroid lesions, negative expression of TPO was seen in 63.16%, 0% and 33.33% of PTC, FCT, and MCT respectively. HBME-1 showed negative expression in 83.3% of cases of benign thyroid lesions. Whereas, in malignant thyroid lesion HBME-1 expression was positive in 78.95%, 50% and 0% cases of PTC, FCT, and MCT respectively. Conclusion: Testing for expression of HBME-1 has been shown to improve the diagnostic accuracy for thyroid malignant nodules. The combination of HBME-1, and TPO may contribute to an accurate diagnosis of papillary thyroid carcinoma.